(untitled) (Research, Society and Development, 2020)
The search for materials with a high degree of purity and crystallization will impact the technological industrial era due to the various applications. However, it is important to look for synthetic methods that are more economical and efficient. In this sense, Ca(0.5)Sr(0.5)MoO4 crystals were synthesized by the coprecipitation method and processed in a hydrothermal microwave oven using different solvent ratios (H2O/C2H6O2), in order to obtain the crystals with high degree of crystallization. The synthesized crystals were characterized by X-ray powder diffraction, lattice parameters, ultraviolet-visible spectroscopy and photoluminescence measurements. The X-ray patterns showed that the crystals have a long-range structural organization, free of secondary phase. The network parameters of the unit cell obtained in this work are very close to the respective values ​​of the JCPDS file nº 30-1287, with some variations that may be related to the synthesis method. The measurements of UV-vis absorption showed the values ​​of the optical band gap as a function of the proportions of solvents ranging from 3.92 to 4.26 eV. The photoluminescence spectra showed broadband with maximum emissions ranging from blue to green. Finally, Ca(0.5)Sr(0.5) MoO4 can be successfully obtained by the methodology used and the use of different proportions of solvents (H2O/C2H6O2) interferes with the optical behavior of the material.